An Online Resource for Improving Instructional Practice - Daniel Stiffler; Mary Frazier (The Advocate, 2016)
Effective teachers are continually looking for engaging teaching strategies, but both new and experienced teachers can feel overwhelmed by the plethora of theories and strategies available to them. The website, K-12Toolbox.org, contains a series of research-based guiding questions coupled with targeted videos, articles, and resources for improving instructional practice. The K-12toolbox.org site will provide easily accessible support for teachers and administrators as they work together to provide classroom lessons that mirror best practice and engage students.